The devil's own - Gordon, Lawrence; Pakula, Allan J. ([Los Angeles, Ca] : Columbia Pictures Industries, 2000)
One of the top Northern Ireland IRA terrorists escapes to New York where he, under a false name, lives in the house of an Irish cop who knows nothing about his real identity. Their surprising friendship and the cop's growing suspicions force the terrorist to choose between the promise of peace or a lifetime of murder
Executive producer, Lloyd Levin ; script, Kevin Jarre
Cast: Harrison Ford, Brad Pitt
VCD format
Keywords: Male friendship in motion pictures; Men in motion pictures